ROLE OF DIFFERENTIAL EQUATIONS IN SOLVING ECONOMIC PROBLEMS (American Journal of Interdisciplinary Research and Development, 2023)
The article analyzed research in the field of models and equations used to analyze economic growth, investment, consumption and other important aspects of economics., as well as the role of differential equations in solving economic problems.